Villarrealina historiographical production: times, spaces and themes addressed - Vega Loyola, José Javier (2023)
An analysis of 186 theses and research papers supported to opt for the Bachelor of History, at the Federico Villarreal National University, between 1988 and 2020, is carried out with the purpose of specifying preferences for periods, spaces and historical themes addressed. As these copies were not preserved in the respective archives, a personal search was carried out with authors, advisers and juries, managing to restore the total corpus of the 186 works. For the analysis, cataloging sheets, follow-up sheets and analysis matrices were prepared. It was found that the preference is highly favorable to the republican period with 66.64%, the viceregal period represents 30.60% and no work for the pre-Hispanic period. Regarding the historical space, the preference is highly favorable to the province of Lima with 49.46%, another 30 provinces together make 16.12%. The preference for historical theme is social history with 40.32%, followed by cultural history with 24.19%, political history with 20.04%, economic history with 9.14% and archival history with 4.30%. It is concluded that Villarreal's historiography is preferably republicanist focused on the 20th century, with little interest in the viceregal period and no interest in the pre-Hispanic period; He is from Lima and with little interest in other provinces such as Cuzco, Chancay, Huamanga, Huarochirí, Huancavelica and Huánuco, eight other provinces have a job for each one, and the rest of the country, mainly the Amazon, is ignored.